Phenotype of cleft lip and palate and other oral manifestations in individuals from the same family - Case reports - Carvalho, Lúcia Rosa Reis de Araújo; Silva, Markelane Santana; Sousa, Heloísa Clara Santos; Prado Junior, Raimundo Rosendo; Mendes, Regina Ferraz (Journal of Oral Diagnosis, 2018)
We aim to describe the oral phenotype and manifestations of the cleft lip and palate of individuals from two generations of a family. The family history, information relating to pregnancies, sociodemographic data and pre- and postoperative clinical and radiographic characteristics of the individuals were collected. Four members of the family had cleft lip and palate: the father and three daughters. They had different phenotypes regarding their type and affected side. The individuals underwent medical treatment and received surgical correction procedures. Alteration in the number, shape, positioning and eruption pattern of teeth was registered. The presence of oral clefts between generations of the same family is not a predictable phenomenon nor are their characteristics. Reports of this nature, as well as the psychological and social impact of the condition, are important to emphasize the need aspects of studies involving these individuals.